Determination of second lactate threshold using near-infrared spectroscopy in elite cyclists - Salas-Montoro, J.- A.; Mateo-March, M.; Sánchez-Muñoz, C.; Zabala, M. (International Journal of Sports Medicine, 2022)
The use of near-infrared spectroscopy could be an interesting alternative to other invasive or expensive methods to estimate the second lactate threshold. Our objective was to compare the intensities of the muscle oxygen saturation breakpoint obtained with the Humon Hex and the second lactate threshold in elite cyclists. Ninety cyclists performed a maximal graded exercise test. Blood capillary lactate was obtained at the end of steps and muscle oxygenation was continuously monitored. There were no differences (p>0.05) between muscle oxygen oxygenation breakpoint and second lactate threshold neither in power nor in heart rate, nor when these values were relativized as a percentage of maximal aerobic power or maximum heart rate. There were also no differences when men and women were studied separately. Both methods showed a highly correlation in power (r=0.914), percentage of maximal aerobic power (r=0.752), heart rate (r=0.955), and percentage of maximum heart rate (r=0.903). Bland-Altman resulted in a mean difference of 0.05±0.27 W·kg-1, 0.91±4.93%, 0.63±3.25 bpm, and 0.32±1.69% for power, percentage of maximal aerobic power, heart rate and percentage of maximum heart rate respectively. These findings suggest that Humon may be a non-invasive and low-cost alternative to estimate the second lactate threshold intensity in elite cyclists.